The Surprising Effects of the Great Recession : Losers and Winners in Thailand in 2008-2009 - Khandker, Shahidur R.; Haughton, Jonathan (World Bank, Washington, DC, 2014)
In 2009, buffeted by the great recession, Thai gross domestic product fell by 2.3 percent. Using monthly data from the socio-economic surveys of 2007-2010, this paper finds, after controlling for household variables, that real consumption per capita rose in 2009 relative to 2008 for most groups, including the poor, urban and rural households, men, women, and children. The losers were residents of Bangkok, especially those aged 20-29, and those working in sales and services. During the recession year of 2009, school enrollment rates did not fall, and durable goods purchases actually rose; households probably reduced their savings, and also benefitted from the lower food prices that prevailed in 2009. A simulation exercise based on the slowdown in growth of gross domestic product would have missed these effects, as would models based solely on readily-available data series. This points to the importance of country-specific policy analysis, rooted in timely local evidence, including household survey data.